Anatomy of falling‐stage deltas in the Turonian Ferron Sandstone of the western Henry Mountains Syncline, Utah: Growth faults, slope failures and mass transport complexes. Issue 1 (20th September 2014) - Fielding, Christopher R.; Hampson, Gary
Abstract Falling‐stage deltas are predicted by sequence stratigraphic models, yet few reliable criteria are available to diagnose falling‐stage deltaic systems in surface exposures. Recent work on the Upper Cretaceous (Turonian) Ferron Sandstone in the western Henry Mountains Syncline of south‐central Utah has established its environment of deposition as a series of modest‐sized (5 to 20 km wide), probably asymmetrical, mixed‐influence deltas ('Ferron Notom Delta') that dispersed sediment eastwards from the rising Sevier orogenic hinterland into the Western Cordilleran Foreland Basin. Analysis of sandstone body stacking patterns in a 67 km long, depositional strike‐parallel (north–south) transect indicates that the growth of successive deltas was strongly forced by synsedimentary growth of a long wavelength (ca 100 km), 50 m amplitude fold structure. Herein, two discrete areas within this transect, superbly exposed in three dimensions, are documented in order to determine the details of stratal stacking patterns in the depositional dip direction, and thereby to assess the stratigraphic context of the Ferron Notom Delta. In the two study areas, dip transects expose facies representing river mouth bar to distal delta front environments over distances of 2 to 4 km. Key stratal packages are clinothems that offlap, downlap, and describe descending regressive trajectories with respective to basal and top datums; they are interpreted as the product of relative sea‐level fall. The vertical extent of clinoforms suggests that deltas prograded into <30 m of water. Furthermore, these deltaic successions preserve abundant evidence of delta front slope failure, growth faulting, and incision and filling of deep (<15 m) slope gullies. Gully fills are composed of chaotic intraformational breccia and/or massive sandstone, and constitute linear, 'shoestring' sandbodies in the distal portions of individual palaeodelta systems. They are interpreted to have been cut and filled during the late falling‐stage and lowstand of relative sea‐level cycles. The north–south distribution of the stratal style described above seems to be focused on the flanks of the growth anticline, and so the numerous falling‐stage systems tracts preserved within the Ferron Notom Delta probably owe their origin to synsedimentary structural growth, and the unstable fluid pressure regime that this growth imposed on the sea floor and shallow subsurface.